GAMBARAN PERILAKU JAJAN DAN AKTIFITAS FISIK PADA SISWA SEKOLAH DASAR DI SDN ORO-ORO OMBO 02 KOTA BATU - Kurniawan, Febrianto Heri; Saichudin, Saichudin; Merawati, Desiana (Jurnal Sport Science, 2016)
Abstract :The purpose of this study is to (1) know the behavior of students at grade 4 and 6 in SDN Oro-Oro Ombo 02 Kota Batu; (2) to know the physical activity of grade 4 and 6 students in SDN Oro-Oro Ombo 02 Kota Batu; (3) to know the nutritional status of grade 4 and 6 students in SDN Oro-Oro Ombo 02 Kota Batu; (4) analyzing the behavior of snack and physical activity in grade 4 and 6 students in SDN Oro-Oro Ombo 02 Kota Batu. Based on the data obtained, the researcher can conclude that from 45 students of Grade 4 and Grade 6 students in SDN Oro-Oro Ombo 02 Batu City with (1) good snack behavior with 20 children with percentage 44,4%, classification less With the number of 19 children with a percentage of 42.2%, the classification of excess with the number of 6 children with the percentage of 13.3%. (2) While children with physical activity classification of light physical activity with 35 children with percentage of 77,7%, classification of moderate physical activity with number of 10 children with percentage of 22,2%. (3) The nutritional status of the students was obtained by the data with nutritional status based on normal BMI with the number of 16 children with the percentage of 35,6%, lean with 22 children with the percentage of 48,9%, the fat with the number of 5 children with 11,1% percentage, Obesity with the number of children with a percentage of 4.4%.Key words :Snacking behavior, physical activity, nutritional status